Effect of ribavirin on viral kinetics and liver gene expression in chronic hepatitis C. Issue 1 (8th February 2013) - Rotman, Yaron; Noureddin, Mazen; Feld, Jordan J; Guedj, Jeremie; Witthaus, Michael; Han, Hwalih; Park, Yoon J; Park, Su-Hyung; Heller, Theo; Ghany, Marc G; Doo, Edward; Koh, Christopher; et al.
Abstract : Objective: Ribavirin improves treatment response to pegylated-interferon (PEG-IFN) in chronic hepatitis C but the mechanism remains controversial. We studied correlates of response and mechanism of action of ribavirin in treatment of hepatitis C. Design: 70 treatment-naive patients were randomised to 4 weeks of ribavirin (1000–1200 mg/d) or none, followed by PEG-IFNα-2a and ribavirin at standard doses and durations. Patients were also randomised to a liver biopsy 24 h before or 6 h after starting PEG-IFN. Hepatic gene expression was assessed by microarray and interferon-stimulated gene (ISG) expression quantified by nCounter platform. Temporal changes in ISG expression were assessed by qPCR in peripheral-blood mononuclear cells (PBMC) and by serum levels of IP-10. Results: After 4 weeks of ribavirin monotherapy, hepatitis C virus (HCV) levels decreased by 0.5±0.5 log10 (p=0.009 vs controls) and ALT by 33% (p<0.001). Ribavirin pretreatment, while modestly augmenting ISG induction by PEG-IFN, did not modify the virological response to subsequent PEG-IFN and ribavirin treatment. However, biochemical, but not virological, response to ribavirin monotherapy predicted response to subsequent combination treatment (rapid virological response, 71% in biochemical responders vs 22% non-responders, p=0.01; early virological response, 100% vs 68%, p=0.03; sustained virological response 83% vs 41%, p=0.053). Ribavirin monotherapy lowered serum IP-10 levels but had no effect on ISG expression in PBMC. Conclusions: Ribavirin is a weak antiviral but its clinical effect seems to be mediated by a separate, indirect mechanism, which may act to reset IFN-responsiveness in HCV-infected liver.